Contribution of European forests to safeguard wild honeybee populations. Issue 2 (28th November 2019) - Requier, Fabrice; Paillet, Yoan; Laroche, Fabien; Rutschmann, Benjamin; Zhang, Jie; Lombardi, Fabio; Svoboda, Miroslav; Steffan‐Dewenter, Ingolf
Abstract: Recent studies reveal the use of tree cavities by wild honeybee colonies in European forests. This highlights the conservation potential of forests for a highly threatened component of the native entomofauna in Europe, but currently no estimate of potential wild honeybee population sizes exists. Here, we analyzed the tree cavity densities of 106 forest areas across Europe and inferred an expected population size of wild honeybees. Both forest and management types affected the density of tree cavities. Accordingly, we estimated that more than 80, 000 wild honeybee colonies could be sustained in European forests. As expected, potential conservation hotspots were identified in unmanaged forests, and, surprisingly, also in other large forest areas across Europe. Our results contribute to the EU policy strategy to halt pollinator declines and reveal the potential of forest areas for the conservation of so far neglected wild honeybee populations in Europe.